Recognizing emotions in speech makes you more credulous - Duran, Geoffrey (The journal of forensic psychiatry & psychology, 2021)
The individual differences determining the ability to detect lies are poorly understood. This study investigated the predictive power of self-monitoring, lexical access, lexico-semantic processes, emotional prosody perception, discourse comprehension, mental imagery and attention on the ability to discriminate lies from truth and on response tendencies in a lie detection task. One hundred and four participants (50% female) were asked to listen to audio-recordings of people describing a relative (50% deceptive) and to judge whether each of them was lying or telling the truth. Participants were also asked to perform several auditory tasks assessing above-mentioned processes and also completed the Self-Monitoring Scale. Multiple regression analyses showed that emotional prosody perception predicted truth bias and that performance in the mental imagery task tended to predict the ability to distinguish truth from lies. These results suggest that competence in emotion recognition leads to label statements as being truthful.